Acridine based metal–organic framework host–guest featuring efficient photoelectrochemical-type photodetector and white LED. Issue 30 (26th July 2022) - Wang, Hua-Rui; Tian, Xu-Ke; Zhang, Ji-Rui; Wen, Meng-Yao; Yang, Xiao-Gang
Abstract : The host–guest interactions, charge transfer and photophysical performance of acridine based MOF were well studied, which can be applied as efficient photodetector and white LED. Abstract : A novel metal–organic framework (MOF) host–guest material [Cd3 (EtOIPA)4 (HAD)2 ]·H2 O has been successfully synthesized by the reaction of 5-ethoxyisophthalic acid (EtOIPA), acridine (AD) and Cd(ii ) salts under hydrothermal conditions. Structurally, the title MOF possesses a trinucleate Cd(ii ) based 2D double-layer with the protonated AD cations as the template encapsulated into the grids. The combination of experiments and theoretical calculations reveals that the orderly arrangement of EtOIPA dimers, protonated AD cations and trinucleate Cd(ii ) clusters generates highly delocalized π-electron channels with a prolonged exciton lifetime. The MOF powders show bright yellow emission with a long lifetime of 50.63 ns. Photoelectrochemical measurements reveal a high photocurrent density ratio of 290 between light and dark conditions at 0 V bias potential, making it a perfect self-driven photodetector. By coating the yellow phosphor on a commercially available blue LED, a high performance white LED with CIE, CCT and CRI values of (0.325, 0.336), 88.2 and 5844 K, respectively can be obtained.